2003
DOI: 10.1111/1469-7610.00150
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial functioning of children and spouses of adults with ADHD

Abstract: The results underscore the strong genetic contribution to ADHD and the need to carefully assess the non-ADHD parent as they seem to influence the well-being of non-ADHD children in families with an ADHD parent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
100
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 29 publications
11
100
1
5
Order By: Relevance
“…The peer relationships of typicallydeveloping children may be less affected by parental ADHD, because these children may naturally make friends without parental coaching. Consistent with this hypothesis, Minde et al (2003) reported that parental ADHD was associated with poorer parent-rated social adjustment if the child also had ADHD and not if the child was typicallydeveloping.…”
Section: Interactions Between Adult and Child Adhd In Shaping Child Smentioning
confidence: 70%
“…The peer relationships of typicallydeveloping children may be less affected by parental ADHD, because these children may naturally make friends without parental coaching. Consistent with this hypothesis, Minde et al (2003) reported that parental ADHD was associated with poorer parent-rated social adjustment if the child also had ADHD and not if the child was typicallydeveloping.…”
Section: Interactions Between Adult and Child Adhd In Shaping Child Smentioning
confidence: 70%
“…The negative correlation between paternal hyperactivity and anxiety in the offspring may be somewhat related to the findings of Minde et al [63] who demonstrated that wives of men with ADHD were more supportive and tolerant with their husbands compared with non-ADHD men married to ADHD women. Agha et al [59] reported that mothers tend to be warmer to ADHD offspring when fathers have ADHD in comparison to the inverse situation.…”
Section: Parental Adhd Symptoms and Offspring Anxiety And Depressionmentioning
confidence: 78%
“…The family dynamic can be further influenced by a parent's psychiatric status. Minde and colleagues 116 found that children with an ADHD parent had higher rates of psychopathology and higher risk of comorbidities. Family and marital functioning are impaired by the presence of an affected parent regardless the gender.…”
Section: Clinical Applications Family Historymentioning
confidence: 99%